2015
DOI: 10.1001/jamapsychiatry.2015.0737
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Sensory Overresponsivity in Youth With Autism Spectrum Disorders

Abstract: IMPORTANCE More than half of youth with autism spectrum disorders (ASDs) have sensory overresponsivity (SOR), an extreme negative reaction to sensory stimuli. However, little is known about the neurobiological basis of SOR, and there are few effective treatments. Understanding whether SOR is due to an initial heightened sensory response or to deficits in regulating emotional reactions to stimuli has important implications for intervention.OBJECTIVE To determine differences in brain responses, habituation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

29
224
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(274 citation statements)
references
References 43 publications
29
224
0
2
Order By: Relevance
“…These individuals also show decreased neural habituation to sensory stimuli and lack prefrontal inhibition of the amygdala during exposure to sensory stimuli. 10 Taken together, these results suggest that SOR may be related to overattribution of salience to extraneous sensory information, as well as to an inability to down-regulate the brain’s responses to this information, thus leading to over-attention towards sensory information. Therefore, we hypothesized that within youth with ASD, individual differences in SOR would be related to extent of connectivity with the salience network, particularly that higher SOR would be related to greater connectivity within the salience network (i.e., with the amygdala), and between the salience network and areas related to primary sensory processing.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…These individuals also show decreased neural habituation to sensory stimuli and lack prefrontal inhibition of the amygdala during exposure to sensory stimuli. 10 Taken together, these results suggest that SOR may be related to overattribution of salience to extraneous sensory information, as well as to an inability to down-regulate the brain’s responses to this information, thus leading to over-attention towards sensory information. Therefore, we hypothesized that within youth with ASD, individual differences in SOR would be related to extent of connectivity with the salience network, particularly that higher SOR would be related to greater connectivity within the salience network (i.e., with the amygdala), and between the salience network and areas related to primary sensory processing.…”
Section: Introductionmentioning
confidence: 85%
“…Recent neuroimaging research suggests that SOR may be related to an over-attribution of salience to extraneous sensory information. 9,10 Thus, in the present study we sought to examine how intrinsic connectivity in the salience network relates to SOR by integrating resting-state functional magnetic resonance imaging (fMRI), task-based fMRI, and behavioral data, to test the assumption that atypical functional connectivity in ASD is directly related to altered brain activity during information processing, as well as to provide insight into SOR, an important source of heterogeneity and impairment in ASD that has as yet received little attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory processing deficits are commonly observed in ASD (Green et al, 2015), but the underlying cellular mechanisms remain unclear. Fragile X syndrome (FXS) is a leading known inherited form of ASD affecting ~1 in 4000 males and 1 in 8000 females (Sherman 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Especially if presented simultaneously across several sensory modalities, which is often the case in face-to-face social intercourse, they may overload their processing capacity and lead to a cognitive and behavioral "shut-down." Studies have shown that this sensory overresponsivity (SOR) is predicated on a hyperactivity in areas related to primary sensory processing, emotional regulation, and response to threat (Green et al 2015). 37 A similar, but less pronounced, inhibitory role is played by the freeze reflex, which seems to be driven by GABAergic and cholinergic neurotransmission (Power and McGaugh 2002;Jhou 2005).…”
mentioning
confidence: 99%